2016
DOI: 10.1515/plm-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation of a professional tattooing procedure and evolutionary study of the skin damage provoked

Abstract: Objective:A clinical observation of a professional tattooing procedure and the skin damage caused by the tattooing technique and the healing process of the lesions.Materials and methods:Three tattoos were performed using black, red and white ink, together with a fourth “tattoo” with the same characteristics and an identical procedure, but using no ink. The evolution of the lesions was observed over a period of 6 months using photographs and biopsies.Results:The tattoos evolved with no complications. At 72 h, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Accordingly, this animal model is often preferred during skin research 29. Biopsies of tattooed skin of volunteers30 show the same histological pattern of tattoos performed on the animals of the present study (figure 1B), which reinforces the results found. In addition, according to the literature, the inflammatory reaction triggered by the introduction of pigment into the skin of the animals follows the same basic pattern in all species 29…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, this animal model is often preferred during skin research 29. Biopsies of tattooed skin of volunteers30 show the same histological pattern of tattoos performed on the animals of the present study (figure 1B), which reinforces the results found. In addition, according to the literature, the inflammatory reaction triggered by the introduction of pigment into the skin of the animals follows the same basic pattern in all species 29…”
Section: Discussionsupporting
confidence: 91%